Encyclopedia of global warming - Dutch, Steven I. (Gale virtual reference library, 2010)
Provides comprehensive coverage of the questions of global warming and climate change, including scientific descriptions and explanations of all factors, from carbon dioxide to sunspots, that might contribute to climate change.